2001
DOI: 10.1086/321464
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐resolvedHubble Space Telescope/STIS Spectroscopy of the Exposed White Dwarf in the High‐Field Polar AR Ursae Majoris

Abstract: Phase-resolved Hubble Space T elescope (HST )/Space Telescope Imaging Spectrograph (STIS) ultraviolet spectroscopy of the high-Ðeld polar AR UMa conÐrms that the white dwarf photospheric Lya Zeeman features are formed in a magnetic Ðeld of D200 MG. In addition to the Lya n and p`components, we detect the forbidden hydrogen transition, which becomes "" enabled ÏÏ in the presence of both 1s 0 ] 2s 0 strong magnetic and electric Ðelds. Overall, the combined ultraviolet and optical low-state spectrum is similar to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 22 publications
2
45
0
Order By: Relevance
“…In addition, they detected the 1s0-2s0 Ly component that violates the parity/magnetic moment rules. This '' forbidden '' line is enforced by the presence of a strong electric field in the atmosphere of the star: it has also been observed in the spectrum of the accreting magnetic white dwarf AR UMa (Gänsicke et al 2001).…”
Section: Introductionmentioning
confidence: 84%
“…In addition, they detected the 1s0-2s0 Ly component that violates the parity/magnetic moment rules. This '' forbidden '' line is enforced by the presence of a strong electric field in the atmosphere of the star: it has also been observed in the spectrum of the accreting magnetic white dwarf AR UMa (Gänsicke et al 2001).…”
Section: Introductionmentioning
confidence: 84%
“…Gänsicke et al (2002) also found that only two previously known short-period systems with HQS spectra failed to be identified as CVs; this "hit rate" of 90% underlines the extreme efficiency of the HQS of finding short period CVs. Five out of those 18 systems have measured white dwarf temperatures, all of them in the range 11 000-16 000 K (MR Ser, ST LMi, AR UMa, SW UMa, T Leo: Gänsicke et al 2001;Hamilton & Sion 2004;Araujo-Betancor et al 2005b;Gänsicke et al 2005). The remaining 13 systems all have spectra dominated by strong Balmer and He emission, suggesting accretion rates too high to detect the white dwarf.…”
Section: Post-bounce Cvs Expected In the Hqsmentioning
confidence: 99%
“…The polar AR Ursae Majoris (AR UMa) is inferred to contain a white dwarf (WD) that possesses a magnetic field of ∼240 MG-the strongest of the known polars (Schmidt et al 1996;Gänsicke et al 2001). Its optical observations show that it often changes between high and low brightness states, remaining in the low state for approximately 90% of the time.…”
Section: Introductionmentioning
confidence: 99%
“…However, if they are present, some might perhaps have been disguised by the emission lines from the MD (e.g., Mg I and Ca II). Here we re-examine the far-ultraviolet spectra in Gänsicke et al (2001), and fit the strongest metal absorption line of Si II with a Gaussian function plus a line. The result shows that the FWHM is 240±80 km s −1 , which is similar to that of the aluminum absorption doublet.…”
mentioning
confidence: 99%